Naloxone Nasal Spray Co-Prescription for the Prevention of Opioid Overdose Complications - Raju, Princy (My University, 2021)
Background: Opioid overdose is becoming a global epidemic. According to Centers for Disease Control and Prevention (CDC), 67,367 drug overdose deaths occurred in the United States (US) in 2018. The US Food and Drug Administration(FDA) approved Naloxone nasal spray as a life saving measure to reverse the effect of narcotic overdose in community settings. Purpose: The purpose of this Doctor of Nursing Practice (DNP) project was to implement an educational intervention to increase Naloxone spray co-prescription, at least by 5% during a two months period, in a primary care setting. Methods: An educational intervention was conducted to teach providers and staff regarding the implications of Naloxone nasal sprays in narcotic overdoses and to encourage co-prescriptions of Naloxone. Pre and post questionnaire were given to measure the effectiveness of education. The IOWA Model of Evidence-Based Practice Implementation was used as the implementation framework and chart reviews were used to track the number of narcotic and Naloxone prescriptions. Results: The findings revealed increased motivation, awareness, confidence, and knowledge with Naloxone co-prescription. The chart audit showed that out of 27 narcotic prescriptions during an eight-week period, 24 Naloxone prescriptions were written, which is 89% of compliance in co-prescription. Implications for Practice: The findings of this DNP project indicate that the co-prescription of Naloxone can be promoted by educating providers on the significance of the intervention, thereby increasing the safety of the patients, reducing health care expenses, and upholding nursing values.
Keywords: Narcotic overdose, Naloxone nasal spray, co-prescription, provider education, community settings